Suppressing Electromagnetic Interference in Switching Converters by Chaotic Duty Modulation: - Song, Yuhong (VDI Verlag, 2017)
The switching converter generates serious electromagnetic interference (EMI), which impairs other devices‘ performance and harms human being’s health. As a way of chaos technique, chaotic modulation has been developed to suppress EMI of the switching converter by dispersing the energy into a wide frequency band and smoothing the peaks of the EMI spectrum. Unlike the well-studied chaotic frequency modulation, the chaotic duty modulation is concerned in this dissertation, which is just to change the duty of the transistor driving-pulse while maintains the fixed switching frequency. Chaotic duty modulation is realized by appending an external chaotic signal to the existing PWM module of the switching converter, which is practicable without the loss of the generality. It is thus verified that this proposal of using chaotic duty modulation in switching converters for EMI suppression is feasible and lays a foundation for industrial applications....